Clinical role of lung ultrasound for diagnosis and monitoring of COVID‐19 pneumonia in pregnant women. (1st July 2020) - Buonsenso, D.; Raffaelli, F.; Tamburrini, E.; Biasucci, D. G.; Salvi, S.; Smargiassi, A.; Inchingolo, R.; Scambia, G.; Lanzone, A.; Testa, A. C.; Moro, F.
ABSTRACT: Lung ultrasound has been suggested recently by the Chinese Critical Care Ultrasound Study Group and Italian Academy of Thoracic Ultrasound as an accurate tool to detect lung involvement in COVID‐19. Although chest computed tomography (CT) represents the gold standard to assess lung involvement, with a specificity superior even to that of the nasopharyngeal swab for diagnosis, lung ultrasound examination can be a valid alternative to CT scan, with certain advantages, particularly for pregnant women. Ultrasound can be performed directly at the bed‐side by a single operator, reducing the risk of spreading the disease among health professionals. Furthermore, it is a radiation‐free exam, making it safer and easier to monitor those patients who require a series of exams. We report on four cases of pregnant women affected by COVID‐19 who were monitored with lung ultrasound examination. All patients showed sonographic features indicative of COVID‐19 pneumonia at admission: irregular pleural lines and vertical artifacts (B‐lines) were observed in all four cases, and patchy areas of white lung were observed in two. Lung ultrasound was more sensitive than was chest X‐ray in detecting COVID‐19. In three patients, we observed almost complete resolution of lung pathology on ultrasound within 96 h of admission. Two pregnancies were ongoing at the time of writing, and two had undergone Cesarean delivery with no fetal complications. Reverse transcription polymerase chain reaction analysis of cord blood and newborn swabs was negative in both of these cases. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. Abstract : Linked article: There is a comment on this article by Quarato et al. Click here to view the Correspondence. Linked article: There is a comment on this article by Sperandeo and Trovato . Click here to view the Correspondence.